Credit spreads, economic activity and fragmentation - Roberto De Santis (European Central Bank (ECB), 2016)
Credit spreads may be jointly driven by developments that are orthogonal to the current state of the economy. We show that this unobserved systematic component is demanded to hedge against adverse economic fl?uctuations. Using either yield-to-maturity spreads or asset swap spreads for 2345 Eurobonds across euro area non-fi?nancial industries, we estimate a market-wide relative excess bond premium - a function of the unobserved systematic component -, which can predict real economic activity, the stock market and survey-based economic sentiment. This premium was highly negative between March 2003 and June 2007 in all bond segments and turned positive since then up to the launch of the 3-years long term refinancing operations in December 2011, predicting the financial crisis and the two recessions. Finally, using the countries?excess bond premia, we fi?nd that fragmentation risk increased sharply after Lehman?s bankruptcy and during the sovereign debt crisis.
Keywords: C32; F36; G12; G15; 330; corporate credit spreads; forecasts; fragmentation; sentiment